Analisis Kualitas Pelayanan Asrama bagi Peserta Didik SMA Negeri 3 Kayuagung Provinsi Sumatera Selatan - Herlina Herlina (Universitas Pendidikan Mandalika, 2021)
This study aims to: 1) analyze the quality of service to students who live in the dormitory of SMAN 3 Kayuagung, and 2) describe the supporting factors and barriers to service for students. This research method uses descriptive quantitative method. The sample of this study amounted to 234 students of class X, XI, and XII. Data collection techniques were carried out through questionnaires, interviews, and observations. While the data analysis technique of this research uses the Importance-Performance Analysis (IPA) method. The results of this study found that six indicators whose performance should be improved by the guardian of the SMAN 3 Kayuagung dormitory, including the condition of a satisfactory and comfortable bedroom, the guardian of the dormitory is given rewards to students who have good jobs, students who lose their belongings must be assisted immediately. The kitchen must prepare the dish on time, the students get security guarantees, and good relationships are established by providing services in the dormitory for students. The dormitory guardian can create a home situation for students to face what they have. To provide criminal sanctions for perpetrators, teachers must involve themselves as parenting teachers by helping the guardian of the dormitory.